(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2015)
A study of slow seepage of polar fluids through porous media is made using smoothed continuity equation and Darcy equation in a porous medium. A transformation and approximate solution of the governing equations was carried out and its analysis showed that increase in both porosity and permeability result in an increase in the pressure of the fluid. Comparison with other studies also showed reasonable agreement.